Significance of bronchiolocentric fibrosis in patients with histopathologic usual interstitial pneumonia - Tanizawa, Kiminobu (Histopathology, 2019)
AIMS: To evaluate the clinical significance of bronchiolocentric fibrosis in patients with a histopathologic pattern of usual interstitial pneumonia. METHODS AND RESULTS: Two hundred fifty-two patients with pathological usual interstitial pneumonia pattern were identified. Two hundred fifteen of these patients (215/252) had the multidisciplinary diagnosis of idiopathic pulmonary fibrosis. Prospectively defined clinical, radiologic and pathological features (including bronchiolocentric fibrosis) were recorded, and peripheral blood MUC5B genotype and telomere length were measured. Bronchiolocentric fibrosis was observed in 38% (96/252) of all patients and 33% (72/215) of idiopathic pulmonary fibrosis patients; its presence was associated with a non-IPF diagnosis on multivariate analysis (odds ratio 3.71, [95% confidence interval 1.68–8.19]). Bronchiolocentric fibrosis was not significantly associated with environmental exposures, gastroesophageal reflux, cigarette smoking, or radiologic patterns. There was no significant association of bronchiolocentric fibrosis with MUC5B genotype or telomere length. Bronchiolocentric fibrosis has no significant impact on survival time. CONCLUSIONS: Most patients with bronchiolocentric fibrosis and a histopathologic pattern of usual interstitial pneumonia have idiopathic pulmonary fibrosis. However, this combined fibrotic pattern is associated with a non-idiopathic pulmonary fibrosis multidisciplinary diagnosis with approximately one-quarter of these patients being diagnosed as chronic hypersensitivity pneumonia or unclassifiable interstitial fibrosis. The presence of bronchiolocentric fibrosis in these patients is not significantly associated with presumed clinical risk factors for bronchiolocentric involvement, radiologic findings, MUC5B genotype, telomere length, or survival time.